(untitled) (LACCEI, 2024)
To face the challenges generated by the health emergency, many Peruvian universities implemented digital resources to support the learning processes of written argumentation. However, these resources require further support to generate satisfactory learning outcomes. In this sense, the objective of this research is to analyze the impact of an epistemic-subjective feedback program mediated with digital resources on argumentative writing in university students. The approach is quantitative to compare initial and final values ​​of the effect of the program in two groups (control and experiment). The sample comprised 338 students and the results were analyzed with their own rubric. The results showed that the feedback had a significant impact on the experimental group, since it reached the Outstanding level (17.39) On the other hand, the control group reached the Expected (14.97), which meant that the epistemic-subjective approach with ICT resources, used progressively and rationally for feedback, helped to improve. However, it was possible to verify that the program mainly improved the level associated with the content (pertinence of ideas, in solidity of the explanation and in the relationships of ideas), which allowed students to improve their ability to argue and support their reasons with logical facts.